1989
DOI: 10.1126/science.2543071
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Molecular Defect in a Family with Spondyloepiphyseal Dysplasia

Abstract: Spondyloepiphyseal dysplasias (SED) are a heterogeneous group of inherited disorders characterized by disproportionate short stature and pleiotropic involvement of the skeletal and ocular systems. Evidence has suggested that SED may result from structural defects in type II collagen. To confirm the validity of this hypothesis, the structure of the "candidate" type II collagen gene (COL2A1) has been directly examined in a relatively large SED family. Coarse scanning of the gene by Southern blot hybridization id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
84
1
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(87 citation statements)
references
References 14 publications
0
84
1
2
Order By: Relevance
“…The differentiation into hypertrophic chondrocytes is accompanied with changes in ECM; switching of collagen types from type II to type X and the disappearance of aggrecan and link protein (1,2). Dysfunction of these extracellular macromolecules in mutant mice results in striking skeletal malformation, suggesting their important roles in skeletal formation (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…The differentiation into hypertrophic chondrocytes is accompanied with changes in ECM; switching of collagen types from type II to type X and the disappearance of aggrecan and link protein (1,2). Dysfunction of these extracellular macromolecules in mutant mice results in striking skeletal malformation, suggesting their important roles in skeletal formation (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…The 7.3-kb and 9.2-kb EcoRI fragments containing portions of the human procollagen al(I1) gene were previously isolated, characterized and subcloned in vector PAT 153 [8,91. M13 UM20 and M13 UM21 obtained from International Biotechnologies, Inc. (New Heaven, CT) were used to subclone the KpnI and BumHI subfragments of the 7.3-kb clone for DNA sequence analysis.…”
Section: Plusmidmentioning
confidence: 99%
“…The human procollagen al(I1) gene has been isolated and characterized using a cosmid clone and a series of overlapping genomic clones [8,91. The entire gene spans six large EcoRI fragments with sizes of 4.8, 7.3, 5.2, 9.2, 3.7 and 4.3 kb in the order of 5' end to 3' end of the gene.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that mutations in the COL2Al gene, which encodes the major component of cartilage, cause some rare hereditary cartilage diseases such as spondyloepiphyseal dysplasia and type I1 achondrogenesis-hypochondrogenesis (3)(4)(5)(6). In these disease conditions, abnormality of cartilage is already manifest at an early age.…”
mentioning
confidence: 99%